Modulation of Innate Immune Mechanisms to Enhance Leishmania Vaccine-Induced Immunity: Role of Coinhibitory Molecules - Gannavaram, Sreenivas; Bhattacharya, Parna; Ismail, Nevien; Kaul, Amit; Singh, Rakesh; Nakhasi, Hira L. (Frontiers in Immunology, 2016)
No licensed human vaccines are currently available against any parasitic disease including leishmaniasis. Several anti-leishmanial vaccine formulations have been tested in various animal models including genetically modified live attenuated parasite vaccines. Experimental infection studies have shown that Leishmania parasites utilize a broad range of strategies to undermine effector properties of host phagocytic cells i.e., dendritic cells (DC) and macrophages (M). Further, Leishmania parasites have evolved strategies to actively inhibit TH1 polarizing functions of DCs, and to condition the infected M towards anti-inflammatory/alternative/M2 phenotype. The altered phenotype of phagocytic cells is characterized by decreased production of anti-microbial reactive oxygen, nitrogen molecules and pro-inflammatory cytokines such as IFN-, IL-12 and TNF-α. These early events limit the activation of TH1 effector cells and set the stage for pathogenesis. Further, this early control of innate immunity by the virulent parasites results in substantial alteration in the adaptive immunity characterized by reduced proliferation of CD4+ and CD8+ T cells, and TH2 biased immunity that results in production of anti-inflammatory cytokines such as TGF-, and IL-10. More recent studies have also documented the induction of co-inhibitory ligands such as CTLA-4, PD-L1, CD200 and Tim-3 that induce exhaustion and/or non-proliferation in antigen experienced T cells. Most of these studies focus on viral infections in chronic phase thus limiting the direct application of these results from these studies to parasitic infections and much less to parasitic vaccines. However, these studies suggest that vaccine induced protective immunity can be modulated using strategies that enhance the co-stimulation that might reduce the threshold necessary for T cell activation and conversely by strategies that reduce or block inhibitory molecules such as PD-L1 and CD200. In this review we will focus on the polarization of antigen presenting cells and subsequent role of co-stimulatory and co-inhibitory molecules in mediating vaccine induced immunity using live attenuated Leishmania parasites as specific examples.